Anthropological theory : an introductory history - McGee, R. Jon , 1955-; Warms, Richard L. (McGraw Hill, 2008)
A comprehensive survey of the history of theory in anthropology, this anthology contains commentary in introductions and notes to guide students through excerpts of seminal anthropological works. It provides information needed to understand each article, its central concepts, and its relationship to the social and historical context.